Expression of heme oxygenase-1 in non small cell lung cancer (NSCLC) and its correlation with clinical data - Degese, María Sol (2012)
While changes in heme oxygenase (HO-1) in lung cancer have already been reported, conflicting results were obtained for enzyme expression in human lung cancer specimens. Therefore, the aim of this work was to study HO-1 expression in a large collection of human lung cancer samples. For this purpose, we analyzed the expression of HO-1 in an organized tissue microarray (TMA) and investigated its correlation with clinicopathological data. Ninety-six percent of tumor samples were positive for HO-1, and the expression of HO-1 was significantly higher in cancerous than in non-cancerous tissues. Importantly, HO-1 expression correlated with advanced stages and lymph node involvement. Additionally, quantitative RT-PCR in 18 pairs of human lung carcinomas and their adjacent non-malignant tissues was performed. Our results demonstrate that HO-1 protein is upregulated in epithelial malignant cells in NSCLC and its expression is associated with higher stages of the disease. Additionally, different subcellular localization is observed between tumor and adjacent non-malignant tissues.